A preliminary study of the application of the transductal velocity ratio for assessing persistent ductus arteriosus. Issue 3 (1st May 2000) - Davies, M W; Betheras, F R; Swaminathan, M
Abstract : OBJECTIVE: To compare the transductal velocity ratio (TVR) of the persistent ductus arteriosus (PDA) with other echocardiographic criteria for haemodynamic significance of a PDA. METHODS: This was a prospective study (from January 1997 to August 1998) in the nurseries of the Royal Women's Hospital, Melbourne. Infants with a clinically suspected PDA were eligible and included if the echocardiogram showed a PDA with a structurally normal heart and the TVR had been measured. The PDA was assessed for evidence of left heart dilatation, the presence of reverse or absent diastolic flow in the descending aorta, the pattern of Doppler flow velocity waveform in the ductus arteriosus, and subjective assessment of ductal diameter on the real time image. The peak systolic velocity (PSV) was obtained from the pulmonary and aortic ends of the PDA, and the TVR calculated by dividing the PSV at the pulmonary end by the PSV at the aortic end. RESULTS: Forty two infants had 59 echocardiographs with their TVR calculated. Mean (SD) birth weight was 1008 (362) g. Mean (SD) gestational age at birth was 27.4 (2.2) weeks with a mean (SD) corrected gestational age of 28.7 (2.7) weeks. The mean TVR was decreased in those infants with a high left atrial diameter/aortic diameter (LA/Ao) ratio (1.9 v 2.8, p = 0.0032) or reverse/absent diastolic flow in the descending aorta (2.1 v 3.0, p = 0.02). This difference was greater if those two criteria were combined (1.7 v 3.4, p = 0.0027). The mean TVR was decreased in infants with a wide open duct seen on two dimensional imaging (1.5 v 3.0, p < 0.0001) or pulsatile flow seen on pulsed Doppler in the PDA (1.9 v 3.4, p = 0.0001). The LA/Ao and left ventricle internal diameter/aortic diameter (LVIDd/Ao) ratios were higher in the group with a TVR < 1.8 than in the other two groups; these differences were statistically significant. CONCLUSIONS: The TVR as a measure of the degree of constriction of a PDA is associated with other echocardiographic criteria for a haemodynamically significant PDA. A low TVR (signifying a poorly constricted duct) is associated with echocardiographic features of a significant left to right shunt, and vice versa. Further research is required to determine the usefulness of the TVR in predicting closure or likely continuing patency of a PDA and the need for treatment.